Calcified aneurysm of the hepatic artery itself: endarterectomy, cholecystectomy - del Campo, Juan C; Castiglioni, Dinorah; Comas, Enrique J (Cirugía del Uruguay, 2020)
A case of calcified aneurym of the hepatic artery is discussed which from the cholecystographical point of view showed as a calculus lodged in the cystic canal. It was solved surgically by performing an endarterectomy and reconstruction of the arterial wall. Excellent postoperatory recovery of the (female) patient.